Pengembangan Modul Tematik Tanaman di Sekitarku Berbasis Kontekstual di Kelas 1 SD - Icha Erpiani; Nurlaeli Nurlaeli; Tastin Tastin; Faisal Faisal; Ahmad Syarifuddin (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
This study aims to: (1) produce a valid contextual-based plant thematic module around me in grade 1 SD /MI, (2) Produce a contextual-based thematic module for plants around me in grade 1 SD /MI that is practical. The type of research used is research and development research. R&D) using the ADDIE development model consisting of analysis, design, development, implementation, and evaluation. The data collection used is a questionnaire and documentation. Test the validity and practicality of the data using the predetermined Likert Scale formula. The subjects of this study were students in grade 1 at SD Negeri 14 Martapura which consisted of 20 people. From the results of the research, the conclusions obtained are: (1) Produce the thematic module of plants around me based on a valid contextual basis seen by the results of the validity of the design validation questionnaire sheet with an average score of 89, material expert validation with an average score of 93, and linguist validation with an average the average score is 98. (2) Produces a contextual-based thematic module of plants around me that is practical as seen from the results of the student response questionnaire of 92.